Analysis of habitat characteristics of the scalloped spiny lobster Panulirus homarus (Linnaeus, 1758) in their home range along the southern coast of Sri Lanka - Senevirathna, J. D. M.; Kodikara, Gayantha R. L.; Munasinghe, D. H. N. (Indian Journal of Fisheries, 2017)
The present study was aimed to investigate the quality of home range habitat characteristics of the scalloped spiny lobster Panulirus homarus (Linnaeus, 1758) in southern coastal region of Sri Lanka. Four sites were selected from south-east (Patanagalle, Godawaya) and south-west (Weligama, Hikkaduwa) regions of the southern coast of Sri Lanka (SCSL). The bottom water quality data and benthic substrate types of their home range habitats were monitored and noted in a 25 x 25 m area covering 16 subsampling points with locality information. With the use of geographical information system (GIS) tools, the spatial distribution maps of environmental parameters were created and submerged bottom substrate types of the four sites were graphed. Salinity, temperature and dissolved oxygen correlated well with depth. Hikkaduwa site was found rich in corals with less number of scalloped spiny lobsters. Sites of south-east region of the SCSL (Patanagalle, Godawaya) were found less polluted having rocks and sandy bottom with high occurrence of scalloped spiny lobsters. Results of the study showed that Patanagalle site (south-east of SCSL) could be suggested as the most suitable site for culturing scalloped spiny lobsters.